The predictive value of ERG protein expression for development of castration‐resistant prostate cancer in hormone‐naïve advanced prostate cancer treated with primary androgen deprivation therapy. Issue 14 (5th June 2015) - Berg, Kasper D.; Røder, Martin A.; Thomsen, Frederik B.; Vainer, Ben; Gerds, Thomas A.; Brasso, Klaus; Iversen, Peter
<x xml:space="preserve">Abstract</x> Background Biomarkers predicting response to primary androgen deprivation therapy (ADT) and risk of castration‐resistant prostate cancer (CRPC) is lacking. We aimed to analyse the predictive value of ERG expression for development of CRPC. Methods In total, 194 patients with advanced and/or metastatic prostate cancer (PCa) treated with first‐line castration‐based ADT were included. ERG protein expression was analysed in diagnostic specimens using immunohistochemistry (anti‐ERG, EPR3864). Time to CRPC was compared between ERG subgroups using multiple cause‐specific Cox regression stratified on ERG‐status. Risk reclassification and time‐dependent area under the ROC curves were used to assess the discriminative ability of ERG‐status. Time to PSA‐nadir, proportion achieving PSA‐nadir ≤0.2 ng/ml, and risk of PCa‐specific death were secondary endpoints. Results Median follow‐up was 6.8 years (IQR: 4.9–7.3). In total, 105 patients (54.1%) were ERG‐positive and 89 (45.9%) were ERG‐negative. No difference in risk of CRPC was observed between ERG subgroups (P = 0.51). Median time to CRPC was 3.9 years (95%CI: 3.2–5.1) and 4.5 years (95%CI: 2.3‐not reached) in the ERG‐positive and ERG‐negative group, respectively. Compared to a model omitting ERG‐status, the ERG‐stratified model showed comparable AUC values 1 year (77.6% vs. 78.0%, P = 0.82), 2 years (71.7% vs. 71.8%, P = 0.85), 5 years (68.5% vs. 69.9%, P = 0.32), and 8 years (67.9% vs. 71.4%, P = 0.21) from ADT initiation. No differences in secondary endpoints were observed. Conclusions ERG expression was not associated with risk of CRPC suggesting that ERG is not a candidate biomarker for predicting response to primary ADT in patients diagnosed with advanced and/or metastatic PCa. Prostate 75:1499–1509, 2015. © 2015 Wiley Periodicals, Inc.